Literature Review: Dinamika Konflik Dalam Organisasi - Putri Arroyyani; Rika NurHalimatus Sholekhah; Novi Aifah Risqiyah; Mu’alimin Mu’alimin (Pusat Riset dan Inovasi Nasional, 2023)
Conflict is a situation involving individuals or groups who are at odds with each other or are in conflict with each other regarding differences in opinion, perception, communication and so on. A conflict does not necessarily occur, but is motivated by sources, symptoms and causes. The aim of this research is to find out and identify what are the sources of symptoms and causes of a conflict in an organization. The method used in this research is the literature review method which is taken from various sources such as magazines, newspapers, internet books and articles. In the literature study method, study related reference books and articles from previous research results that are relevant to the topic of this discussion. The results of this research are that conflict can originate from differences in personality, interactions, structural levels, cultural and ideological differences. In general, the symptoms behind the occurrence of conflict are disagreements between members of groups or organizations, norms that conflict with each other and conflicting actions between groups or organizations. The causes of conflict include communication, personality, limited resources, goals. inconsistent and so on.